Hubungan World Federation of Neurosurgical Societies (WFNS) Subarachnoid Hemorrhage (SAH) Grading Scale dan Mortalitas Pada Pasien Cedera Kepala dengan Perdarahan Subaraknoid di RS Royal Prima Medan - Damanik, Agnes Marwaty; Harahap, Alvin Abrar; Bangun, Primta (Syntax Corporation, 2025)
Head injuries are one of the leading causes of morbidity and mortality in the world, with Subarachnoid Hemorrhage (SAH) being one of the most frequent complications that can increase the risk of death. The World Federation of Neurosurgical Societies (WFNS) Subarachnoid Hemorrhage (SAH) Grading Scale is used to assess the severity of SAH patients and predict their prognosis. This study aims to determine the relationship between WFNS SAH Grading Scale and mortality in head injury patients with SAH at Royal Prima Hospital Medan. The research method used an analytical observational approach with a cross-sectional design. The research sample amounted to 47 patients who met the inclusion criteria, using medical record data for the period January 2023 to August 2025. Data analysis was carried out using the Chi-Square test. The results showed that the majority of patients were in Grade I (38.3%) and Grade IV (27.7%), with a mortality rate of 23.4%. Statistical tests showed a value of p = 0.001 which means that there is a significant relationship between the WFNS SAH Grading Scale and the mortality of SAH patients. The lower the patient awareness level (GCS), the higher the risk of death. This study emphasizes the importance of using the WFNS SAH Grading Scale in assessing prognosis and determining the priority management of SAH patients in hospitals.